Does ethnic diversity affect well-being and allostatic load among people across neighbourhoods in England?. (March 2021) - Li, Danying; Ramos, Miguel R.; Bennett, Matthew R.; Massey, Douglas S.; Hewstone, Miles
Abstract: Modern societies are facing unprecedented changes in their ethnic composition. Increasing ethnic diversity poses critical new challenges as people interact with new cultures, norms, and values, or avoid such encounters. Heated academic and political debates focus on whether and how changes in ethnic composition affect societies and local communities. Yet, there is insufficient scientific evidence of how living in a more diverse society affects individuals' well-being and health. The aim of this study is to test the extent to which increasing neighbourhood ethnic diversity affects individuals' subjective health and well-being and objective stress levels as measured by allostatic load. We analyse a large panel data set containing over 47, 000 English respondents living in 15, 545 neighbourhoods in England from the British Household Panel Survey and the UK Household Longitudinal Study, from 2004 to 2011. We match respondents to neighbourhoods and merge contextual information about levels of neighbourhood ethnic diversity and deprivation from UK Censuses, whilst controlling for background characteristics. We distinguish between short- and long-term effects of ethnic diversity on individual subjective well-being and health as well as allostatic load using a set of multilevel mixed-effects models. We make cautious causal interpretations by estimating fixed-effects models and cross-lagged panel models. We assess the robustness of our findings by replicating our analysis using alternative composite measures of diversity and allostatic load. In the short-term, increasing ethnic diversity of local areas is associated with a dip in subjective well-being, but short-term changes are not prolonged or profound enough to affect chronic stress (allostatic load). The initial negative impact of ethnic diversity on subjective well-being and health dissipates with time. In the long-term, no effects of ethnic diversity on well-being and health or chronic stress (allostatic load) are detected. Understanding the dynamic nature of the effects of ethnic diversity on individuals has critical implications for social and public health policies – issues prominent in, for example, the UK (Brexit) and the US (election of President Donald Trump). Our analysis identifies and enables the promotion of beneficial effects, while targeting the pernicious components to turn diversity into a valuable asset in a globalising world. Highlights: Negative effects of ethnic diversity on subjective well-being dissipate with time. No long-term effects of ethnic diversity on subjective well-being are detected. Objective health measured by biomarkers is not affected by ethnic diversity.